analisis makanan cepat saji bagi kehidupan remaja kota surabaya menggunakan teori fenomenologi - nimah, mufidah wardatun (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2023)
Fast food is one of the innovations created in this modern era. The initial goal of creating fast food was only to meet people's needs, but over time the purpose of fast food was not only to meet people's needs, but there were other purposes and functions. This study aims to examine and analyze in depth the values contained in fast food and explore the perspective of teenagers about fast food in Surabaya. Fast food is an innovation that occurs in this modern era. A phenomenological qualitative approach is used in this study. The results showed that Surabaya teenagers considered that fast food had other functions such as increasing the social status of teenagers and being able to fulfill the fast-paced lifestyle that Surabaya teenagers lived.